Labour market reform in China - Meng, Xin (Trade and development (Cambridge, England), 2000)
Comprehensive analysis of urban and rural labour market reform in China. Documents and analyses institutional changes over the last twenty years and offers evidence that further labour market reform is necessary if China is to sustain its high growth rates. The latest volume in the successful Trade and Development Series.